Asksia AI LOGO

Sia

3159673759's Question
Biology
Posted 6 months ago

6. Determine an equation for the tangent to each curve at the indicated value.
a) f(x)=(x23)(x2+1),x=4f(x)=\left(x^{2}-3\right)\left(x^{2}+1\right), x=-4
b) g(x)=(2x21)(x2+3),x=2g(x)=\left(2 x^{2}-1\right)\left(-x^{2}+3\right), x=2
c) h(x)=(x4+4)(2x26),x=1h(x)=\left(x^{4}+4\right)\left(2 x^{2}-6\right), x=-1
d) p(x)=(x3+2)(4x23),x=3p(x)=\left(-x^{3}+2\right)\left(4 x^{2}-3\right), x=3
Sign in to unlock the answer
Answer from Sia
Posted 6 months ago
I see that you have a question about determining an equation for the tangent to each curve at the indicated value. Let's start with part a) f(x)=(x23)(x2+1),x=4f(x)=\left(x^{2}-3\right)\left(x^{2}+1\right), x=-4. To find the equation for the tangent, we need to take the derivative of the function and then substitute the given value of x into the derivative to find the slope of the tangent. After that, we can use the point-slope form to find the equation of the tangent line. Would you like me to walk

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question